Changes in Attitudes, Intentions, and Behaviors toward Tobacco and Marijuana during U.S. Students' First Year of College - Mara W. Stewart; Megan A. Moreno (SAGE Publishing, 2013)
Tobacco and marijuana are commonly used by college students and have negative health effects. The purpose of this study was to understand how students' attitudes, intentions, and behaviors toward tobacco and marijuana change during freshman year and to examine how attitude and intention predict use of these substances. 275 college students completed phone interviews before and after their freshman year. The identical interviews assessed students' attitudes, intentions, and behaviors toward both substances. Attitudes and intentions increased significantly. 12.2% of participants initiated tobacco use and 13.5% initiated marijuana use. Only intention predicted tobacco initiation, while both attitude and intention predicted marijuana initiation. Overall, attitudes, intentions, and behaviors changed significantly toward favored use. Predictors of use varied by substance, suggesting that different prevention approaches may be beneficial.